PENGEMBANGAN KOMPETENSI PEGAWAI UNTUK MENINGKATKAN KINERJA PEGAWAI PADA KANTOR BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KABUPATEN KUTAI BARAT - Eva Ningsih (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The purpose of this study is to describe and analyze the development of competencies to improve employee performance and identify factors that support and hinder the development of competencies to improve the performance of employees in Finance and Asset Management Agency Region West Kutai. The analysis used is the concept of data analysis proposed by Miles, Huberman and Saldana states in qualitative research, data analysis conducted by three lines of activities occurring simultaneously, namely condensation, data presentation and conclusion / verification. The study concluded the competence development of personnel resources is done through formal education by assigning as many as nine people who menyesaikan on graduate programs and of that number are all still in the process of completion of the study. While the development of employee competencies for education and training by assigning employees to follow bimtek and training as much as 5 employees with three types of activities that support the duties and functions of employees BPKAD West Kutai.Keyword: development, competence, BPKAD.